PENYELESAIAN KREDIT MACET KENDARAAN BERMOTOR DENGAN JAMINAN FIDUSIA DI PT. ADIRA DINAMIKA MULTI FINANCE TBK. CABANG SEMARANG 1 - Kashadi, Yuli Prasetyo Adhi, Benyamin Adhi Susanto, (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
The present of consumer finance institutions as an alternative source of financing is considered very helpful people to buy needed goods. One item that is often used as the object of financing is motorcycle. Motorcycle credit agreement is generally loan agreement with the fiduciary. This study aims to investigate the implementation of motorcycle financing with fiduciary in PT. Adira Dinamika Multi Finance Tbk. Cabang Semarang 1 and the measures taken by PT. Adira Dinamika Multi Finance Tbk. Cabang Semarang 1 if there is a bad credit motorcycle. The study is an empirical legal research in which the authors use secondary data sources to analyze the various laws and regulations in the areas of credit, fiduciary rules, also using primary data collected from interviews with Branch Manager PT. Adira Dinamika Multi Finance Tbk. Cabang Semarang 1. The result obtained are lending a motorcycle with a fiduciary in PT. Adira Dinamika Multi Finance Tbk. Cabang Semarang 1 has been accordance with the procedures in the credits, one of which is the in-depth credit analysis by 5C to credit proposed by the prospective borrowers. This is to minimalize the possibility of a bad credit motorcycle with fiduciary. But if it turns out bad credit still happen, PT. Adira Dinamika Multi Finance Tbk. Cabang Semarang 1 made several attempts as do the desk call and fines, granting subpoena, rescheduling, restructuring and over kredit, giving last repayment. If such efforts have been made, but the debtors remain in default, the steps taken byÂ PT. Adira Dinamika Multi Finance Tbk. Cabang Semarang 1 is the withdrawal of the collateral. But the withdrawal of collateral measures are sometimes encountered obstacles in the absence of registration of fiduciary goods in the Fiduciary Registration Office. Consequently, PT. Adira Dinamika Multi Finance Tbk. Cabang Semarang 1 loses their right to execute directly.